2016
DOI: 10.1002/2016gl069835
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the observed and modeled Southern Hemisphere circulation response to volcanic eruptions

Abstract: Confusion exists regarding the tropospheric circulation response to volcanic eruptions, with models and observations seeming to disagree on the sign of the response. The forced Southern Hemisphere circulation response to the eruptions of Pinatubo and El Chichón is shown to be a robust positive annular mode, using over 200 ensemble members from 38 climate models. It is demonstrated that the models and observations are not at odds, but rather, internal climate variability is large and can overwhelm the forced re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…The shutdown of the QBO-like oscillation in this configuration admittedly complicates the analysis (essentially, reducing our effective sample size), but the early evolution of the extratropical response appears to be insensitive to the initial phase of the QBO. annular modes of variability (e.g., Perlwitz and Graf 1995;Bittner et al 2016b;Barnes et al 2016;McGraw et al 2016). The annular modes dominate variability in the extratropical atmosphere in both hemispheres (Thompson and Wallace 2000) and have been linked to the response to external forcings, including greenhouse gases (e.g., Kushner et al 2001) and stratospheric ozone (e.g., Son et al 2010).…”
Section: Seasonality Of the Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The shutdown of the QBO-like oscillation in this configuration admittedly complicates the analysis (essentially, reducing our effective sample size), but the early evolution of the extratropical response appears to be insensitive to the initial phase of the QBO. annular modes of variability (e.g., Perlwitz and Graf 1995;Bittner et al 2016b;Barnes et al 2016;McGraw et al 2016). The annular modes dominate variability in the extratropical atmosphere in both hemispheres (Thompson and Wallace 2000) and have been linked to the response to external forcings, including greenhouse gases (e.g., Kushner et al 2001) and stratospheric ozone (e.g., Son et al 2010).…”
Section: Seasonality Of the Responsementioning
confidence: 99%
“…Furthermore, fewer studies have addressed the Southern Hemisphere (SH) response, where proxy data are scarce. Some studies have found a poleward shift of the SH winter jet (e.g., Karpechko et al 2010;McGraw et al 2016) while again others have found little or opposite response (e.g., Robock et al 2007;Roscoe and Haigh 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (Stenchikov et al, ; Ottera, ) have argued that models overestimate the stratospheric polar vortices, which could affect the tropospheric responses to volcanoes. Additionally, several simulation studies (Karpechko et al, ;Barnes et al, ; McGraw et al, ) have suggested that some large internal variabilities, such as the state of the ENSO, could play a role in the perceived discrepancies between the model results and observations. Both the fifth Coupled Model Intercomparison Project (CMIP5) simulations and Community Earth System Model (CESM) Large Ensemble simulations showed that, in the year following an eruption, a positive ENSO state (El Niño) was correlated with a weaker SAM anomaly whereas a negative ENSO states (La Niña) was correlated with a stronger SAM anomaly (Barnes et al, ; McGraw et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…ENSO remotely influences the SAM through a Rossby wave train and associated effects on storm tracks such that El Niño (La Niña) events generally result in negative (positive) SAM phase (Fogt and Bromwich, ; Fogt et al, ; Abram et al, ). In response to large volcanic eruptions, the stratospheric temperature gradient increases and strengthens the polar vortex, resulting in a significant positive SAM anomaly that propagates from the stratosphere into the troposphere in the 3 years following the eruption (Barnes et al, ; McGraw et al, ). However, internal climate variabilities such as strong El Niño events can weaken or even mask the positive responses in the eruption year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation